COUNSELING ON THE PREVENTION OF VAGINAL DISCHARGE IN ADOLESCENTS WITH PERSONAL HYGIENE AT HIDAYATUN NAJAH SAMIRAN VILLAGE PROPPO SUB-DISTRICT PAMEKASAN DISTRICT - Nuviana Safitri, Nuviana Safitri; Emi Yunita, Emi Yunita (Jurnal Pengabdian Masyarakat DEDIKASI, 2023)
women who experience vaginal discharge as much as 75%, mostly 50% occur in adolescents, 25% in women of childbearing age (WUS). Vaginal discharge in adolescents usually occurs before and after menstruation which is physiological. If the behavior of genital hygiene care is not good, it can be the cause of pathological vaginal discharge which causes discomfort and in the long term can cause pelvic infection and infertility. One of the factors inhibiting healthy behavior is the lack of knowledge and awareness of individuals about genital hygiene including the prevention and treatment of vaginal discharge. The purpose of this activity is to determine the relationship between the knowledge of adolescent girls about vaginal discharge and genital hygiene behavior. The targets of this activity are female students at Hidayatun Najah Mts, Samiran Village, Proppo District, Pamekasan. The evaluation provides an opportunity for female students to ask questions and provides an opportunity to explain again about vaginal discharge. Adolescent girls need to be given information on how to clean the reproductive organs properly and correctly. In addition, it is also necessary to encourage them to actively seek out information about reproductive health, especially providing lessons on genital organ care such as toileting techniques, using underpants that are not tight, changing underpants, and using non-perfumed soap.